Investment policy review : Guatemala (UN New YorkUS, 2011)
Presents an overview of FDI trends. Reviews and assesses the investment framework. Analyses three priority sectors for FDI attraction. Summarises the key findings and presents the main recommendations.
Keywords: INVESTMENT POLICY